2020
DOI: 10.1007/978-3-030-64849-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Does Herding Behaviour Among Traders Increase During Covid 19 Pandemic? Evidence from the Cryptocurrency Market

Abstract: Cryptocurrencies are digital currencies and trading these currencies have gained huge momentum in recent years. The sophisticated features, complexities on regulatory framework, and high volatility of Cryptocurrencies would pose trading challenges to new investors and/or investors with limited knowledge. Investors generally are influenced by fund managers, financial analysts or other investors who are considered as well informed and highly knowledgeable peers. Investors mimic their behaviour to perform trading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…However, the impact of media is reduced when the market returns to a normal phase. This is in line with different studies that use different datasets and time periods [ 125 , 127 , 128 ]. More importantly, the way investors show herding behavior is that they tended to invest in the major and most-tradable cryptocurrencies [ 27 ].…”
Section: Experimental Results and Discussionsupporting
confidence: 89%
“…However, the impact of media is reduced when the market returns to a normal phase. This is in line with different studies that use different datasets and time periods [ 125 , 127 , 128 ]. More importantly, the way investors show herding behavior is that they tended to invest in the major and most-tradable cryptocurrencies [ 27 ].…”
Section: Experimental Results and Discussionsupporting
confidence: 89%
“…However, this result does not indicate the opposite; rather, it indicates adverse herding owing to higher risk aversion during extreme periods (da Gama Silva et al 2019 ). This result is also consistent with previous studies suggesting that herding behavior is obvious during normal periods, whereas it disappears during up and down periods (Susana et al 2020 ). Supporting these findings are Vidal-Tomas et al ( 2019 ) and Papadamou et al ( 2021 ), who state that herding in the cryptocurrency market is stronger during down periods as most cryptocurrencies have experienced extreme price increases during the pandemic.…”
Section: Resultssupporting
confidence: 94%
“…These cryptocurrency market properties may cause uninformed investors to mimic the transactions of other market participants. Previous studies have also provided strong evidence of herding in the cryptocurrency market (Kallinterakis and Wang 2019 ; Vidal-Tomas et al 2019 ; da Gama Silva et al 2019 ; Kaiser and Stöckl 2020 ; Ballis and Drakos 2020 ; Susana et al 2020 ; Papadamou et al 2021 ; among others). More importantly, cryptocurrency investors tend to herd as uncertainty increases (Bouri et al 2019 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the pandemic repercussion on cryptocurrency markets and their role in creating bubbles is considerable in this study. These results follow previous studies that demonstrated that the COVID-19 pandemic is responsible for increasing panic states, changing investor attitudes and herding behavior (Yarovaya et al, 2020;Mnif et al, 2020;Susana et al, 2020).…”
Section: Resultssupporting
confidence: 91%